Implications of the use of different payment models – the context of PPP Road Projects in the UK - Villalba Romero, Félix; Liyanage, Champika (Emerald Insight, 2016)
This paper sets out to illustrate the payment models and financing structures used for road Infrastructure projects under Public Private Partnerships (PPP) in the UK. Comparison of funding and financial structures in the selected case studies exposes the risks and values of the models of payment utilised. This research also aims to identify relationships with payment certainty and financing debt restructuring. The paper compares several case studies representing the evolution of Private Finance Initiative (PFI) road infrastructure in the UK context. Templates were completed using semi- structured interviews during data collection; and a Qualitative Content Analysis (QCA) approach was employed for case study analysis. Lessons learned from using different payment methods show the benefit and limitations of adopting different forms of PPP in road development. Refinancing of projects presents substantial risks to the viability of a project, and benefits gained by the private sector. Further, refinancing brings no significant benefits to the public sector as well. Performance of selected case studies highlights emerging issues that need to be considered when adopting a PPP procurement route in roads projects. Financial markets have supported these projects under different risk profiles and payment models. They also have the potential to play a greater part in capitalising long-term investment in road projects and increase private sector participation in infrastructure development, generating more competition and innovation. This paper provides case study comparison and practical implications of recent PPP developments in road provision in the UK and the evolution of public policy in the subject.
Keywords: Mercados financieros; Payment structures; Private Finance Initiative (PFI); Public Private Partnerships (PPPs); Financial markets; Innovation; Roads